Bibliometric Analysis of “Therapeutic Recreation” Studies with Visual Mapping Technique - KÜL AVAN, Sevim; PARLAKYILDIZ , Sinem (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2025)
The advancement of scientific research contributes to the accumulation of knowledge on any subject it addresses. Therapeutic recreation comprises activities aimed at improving the health and functional status of individuals with special needs, enhancing their quality of life, and facilitating adaptation to life. This study was conducted using bibliometric methods to determine the general structure and development of scientific research in the field of therapeutic recreation. The objective was to comprehensively examine the stages and overall structure of the literature on "therapeutic recreation," identify key themes, and contribute to future research in this area. Within the scope of this study, 1257 research articles were examined using the Scopus database. The types of studies, authors, years, countries, languages, institutions, subject areas, journals, and keywords related to therapeutic recreation were evaluated. The data were analyzed using VOSviewer software. The study examined the development of therapeutic recreation research from 1933 to May 31, 2023. The findings revealed that the majority of studies were in the form of articles, with “Lorna Moxham” identified as the most prolific author. The year 2020 was found to be the peak period for therapeutic recreation research, with the United States being the country with the highest number of studies. It was observed that the studies were predominantly in the English language, and the institution with the highest number of studies was the “University of Wollongong”. The most commonly used keyword was "therapeutic recreation," and the journal with the highest number of publications was identified as the "Therapeutic Recreational Journal". In conclusion, this study provided a comprehensive evaluation of scientific research in the field of therapeutic recreation, highlighting trends and developments. It demonstrated that therapeutic recreation is a multidisciplinary subject studied in various countries and universities, with an increasing number of studies being conducted and regularly reviewed. The study could serve as an important resource for guiding future research in this area and contributing to the literature.